Married and No Sex Anymore: Mbulu As a Pastoral Problem in Mzimba in Northern Malawi - Kamwela, Bonet (Luviri Press, 2020)
Cover -- Copyright page -- Title page -- Contents -- Dedication -- Acknowledgements -- Introduction -- Chapter One - Mbulu in the Traditional Culture of Mzimba -- Mzimba District -- Cultural Beliefs on Mbulu -- Chikhoso or Moto -- Deaths -- Herbs for the Affected Woman -- Sex with Young Men -- How Mbulu Belief is followed in Mzimba -- Sleeping with Grandchildren in the same Room -- Separation of Rooms -- Medication -- Ejaculating Outside -- Sleeping with Clothes on -- The Use of Condoms -- Mitala (Polygamy) -- Why Mbulu Belief is followed in Mzimba -- To Avoid Chikhoso or Moto -- To Avoid Death -- Avoid Shaming the Society -- Mbulu and Biology -- Chapter Two - Mbulu as a Pastoral Problem -- Problems Caused by Mbulu Belief in Marriages -- Mitala (Polygamy) -- Chibwezi (Vibwezi) -- Rape Cases of Granddaughters -- Separation of Rooms -- Breaking of Marriage -- Denial of Resources -- In the Society -- Spread of HIV &amp -- AIDS -- Poor Relationships -- In the Church (CCAP Synod of Livingstonia) -- Losing Church Members -- Absenting themselves from Church -- Problems in Serving God -- Chapter Three - Biblical Teachings Related to Mbulu -- Sex in the Old Testament -- Abstinence from Sex in the Old Testament -- Sex in the New Testament -- Matthew 19:4-6 -- 1 Corinthians 7:1-5 -- Mbulu in the Bible? -- Those against the Mbulu Belief -- Chapter Four: Pastoral Advice -- Advice to Newly Married Couples -- Advice to Modern People -- Advice to Traditionalists -- Advice in Marriage Seminars -- Bibliography -- Published Sources -- Oral Sources -- Back cover.